2012
DOI: 10.1590/s0100-879x2012007500051
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional kinematic analysis of upper and lower limb motion during gait of post-stroke patients

Abstract: The aim of this study was to analyze the alterations of arm and leg movements of patients during stroke gait. Joint angles of upper and lower limbs and spatiotemporal variables were evaluated in two groups: hemiparetic group (HG, 14 hemiparetic men, 53 ± 10 years) and control group (CG, 7 able-bodied men, 50 ± 4 years). The statistical analysis was based on the following comparisons (P ≤ 0.05): 1) right versus left sides of CG; 2) affected (AF) versus unaffected (UF) sides of HG; 3) CG versus both the affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 28 publications
2
31
0
2
Order By: Relevance
“…The same symmetrical behavior was observed looking at the CoM oscillation of the unaffected side. In a previous study of the same research group of the present paper, 4 asymmetric alterations were observed in angular kinematics of lower and upper limbs, as well as asymmetrical lateral trunk motion with respect to zero, in post-stroke patients.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The same symmetrical behavior was observed looking at the CoM oscillation of the unaffected side. In a previous study of the same research group of the present paper, 4 asymmetric alterations were observed in angular kinematics of lower and upper limbs, as well as asymmetrical lateral trunk motion with respect to zero, in post-stroke patients.…”
Section: Discussionsupporting
confidence: 64%
“…The stroke patients presented lower CoM elevation than CG when supporting their weight with the affected limb. Spasticity and muscle weakness are often pathological disturbances from stroke 4 and may be the primary cause of these alterations in the CoM trajectory observed in this study. The total range of CoM motion of the HG was lower than CG in the forward direction as expected since the HG subjects walked slower than CG and consequently covered smaller distance.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…These results are related to the stroke gait features, specially the main alterations found in the affected lower limb joints as decreased ankle, knee and hip flexion/extension range of motion [19].…”
Section: Discussionmentioning
confidence: 84%
“…As a matter of fact, such parameters have been defined and studied in the literature to describe the characteristics of the hemiparetic gait (CARMO et al, 2012;LUCARELI AND GREVE, 2006;CHEN et al, 2003). The peak values of angular trajectories of stroke subjects walking at self-selected speed have been analyzed and it has been found that faster walkers compensated for poor knee flexion and ankle dorsiflexion with larger amounts of circumduction (STANHOPE et al, 2015).…”
Section: Introductionmentioning
confidence: 99%